The sol-gel synthesis and characterzation of strontium titanate doped with Pr and AI ions /lcMutia Suhaibah Abdullah - Mutia Suhaibah Abdullah,ld1985-; Rosli Hussin, supervisor; Fakulti Sains
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010